Paradigma Bhineka Tunggal Ika dan Implikasinya dalam Menangani Tawuran Antar Kelompok - Zainudin Hasan; Bagas Satria Wijaya; M. Faisal Syahputra (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to investigate the Bhinneka Tunggal Ika paradigm and its implications in dealing with brawls between groups in Indonesia. The Bhinneka Tunggal Ika paradigm reflects the spirit of diversity and unity in Indonesia, which is officially recognized as the national motto. However, challenges such as brawls between groups are still a serious problem in society, indicating that the implementation of this paradigm has not been completely successful. This research uses a literature study method to analyze the concept of Bhinneka Tunggal Ika, the factors that influence its implementation in dealing with brawls between groups, as well as strategies that can be implemented to increase its effectiveness. It is hoped that the results of this research will provide better insight into how the Bhinneka Tunggal Ika paradigm can be translated into concrete actions in dealing with inter-group conflicts in Indonesia.